2007
DOI: 10.1111/j.1462-5822.2006.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

An early event in the herpes simplex virus type-2 replication cycle is sufficient to induce Chlamydia trachomatis persistence

Abstract: SummaryEpidemiological studies have demonstrated that co-infections of herpes simplex virus type 2 (HSV-2) and Chlamydia trachomatis occur in vivo. Data from a tissue culture model of C. trachomatis/HSV-2 co-infection indicate that viral co-infection stimulates the formation of persistent chlamydiae. Transmission electron microscopic (TEM) analyses demonstrated that in both HeLa and HEC-1B cells, co-infection caused developing chlamydiae to exhibit swollen, aberrantly shaped reticulate bodies (RBs), characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 51 publications
5
47
0
Order By: Relevance
“…Interestingly, when serovar E was grown in similar conditions and analyzed with the same approach, initial EB-to-RB differentiation was found to occur earlier in endometrial HEC-1B cells compared to endocervical HeLa cells, and higher chlamydial genome and transcript numbers were detected throughout the developmental cycle in the former cell line [13]; these differences were in fact the result of a faster growth of this urogenital strain in the HEC-1B cells, leading to the recovery of ca. 4-10 times more chlamydial progeny compared to HeLa cells [13,14]. Thus, while physiological differences between endometrial and endocervical cells appear to greatly influence the growth of urogenital serovar E, the more invasive serovar L2 grows equally well in both environments.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, when serovar E was grown in similar conditions and analyzed with the same approach, initial EB-to-RB differentiation was found to occur earlier in endometrial HEC-1B cells compared to endocervical HeLa cells, and higher chlamydial genome and transcript numbers were detected throughout the developmental cycle in the former cell line [13]; these differences were in fact the result of a faster growth of this urogenital strain in the HEC-1B cells, leading to the recovery of ca. 4-10 times more chlamydial progeny compared to HeLa cells [13,14]. Thus, while physiological differences between endometrial and endocervical cells appear to greatly influence the growth of urogenital serovar E, the more invasive serovar L2 grows equally well in both environments.…”
Section: Discussionmentioning
confidence: 92%
“…Of note, infectious titers obtained by these authors for genital serovar L2 in conjunctival cells were lower than those in endocervical HeLa cells, although the drop in infectivity was not nearly as dramatic as that for serovar D. Also, very recently, using polarized genital epithelial cells grown in 3D bead cultures, our group found that C. trachomatis serovar E grows faster in endometrial HEC-1B than in endocervical HeLa cells, which resulted in the recovery of ca. 4 times more chlamydial progeny in the former cell line upon completion of the developmental cycle [13]; other authors reported a 10-fold difference in the number of serovar E infectious progeny recovered between these two cell lines [14]. These differences in recoverable bacterial yields are potentially important, as collecting sufficient numbers of chlamydiae for downstream applications can sometimes be challenging and time-consuming, particularly when studying urogenital strains.…”
Section: Introductionmentioning
confidence: 99%
“…trachomatis coinfections have indicated that HSV-2 co-infection alters chlamydial development; however, previous studies did not examine the co-infection process in detail (Chiarini et al, 1996;Pontefract et al, 1989;Superti et al, 2001). Data from a tissue culture model of C. trachomatis and HSV-2 co-infection established in our laboratory indicate that, during C. trachomatis serovar E and HSV-2 co-infection, HSV attachment and/or entry transmits a signal which interrupts the normal chlamydial developmental cycle and induces persistence (Deka et al, 2007). These and other data have led us to hypothesize that HSV attachment to and/or entry activates a novel anti-chlamydial defence pathway in mucosal epithelial cells.…”
Section: Introductionmentioning
confidence: 88%
“…It is well documented that infection with one pathogen can alter the risks of infection with a second pathogen. For example, a recent study has shown that Herpes simplex virus 2 can induce persistence of Chlamydia trachomatis in human female reproductive tract epithelial cells (57).. To determine whether stimulation of FTEC with TLR3 agonist results in the upregulation of other TLR, we exposed FTEC to apical treatments of poly (I:C) for 24 h and prior to measuring the levels of mRNA expression for TLR2, 3, 4, 5, 7, and 9 by real-time RT-PCR. As shown in Figure 6, poly(I:C) treatment resulted in a significant upregulation of TLR2, 3, and 7.…”
Section: Exposure Of Ftec Poly(i:c) Upregulates Tlr2 3 Andmentioning
confidence: 99%